Analysis of Paddy Field Conversion Using Geographic Information System (GIS) in Labuhanbatu Utara Regency, Indonesia - Panjaitan, Ibnu Hasmi; Nasution, Zulkifli; Rujiman (Journal of Environmental and Development Studies, 2023)
The number of paddy production in Labuhanbatu Utara Regency, North Sumatera Province, Indonesia, continues to decline from year to year, partly due to the reduction in the area of paddy fields. This was caused by land conversion from paddy fields to non-paddy fields. This research aims to analyze the pattern of changes in the process of paddy fields to non-paddy fields in Labuhanbatu Utara Regency and its suitability on the regional spatial plan between 2017 and 2021. The research uses a descriptive qualitative method. The data was processed and analyzed using an overlapping method on biophysical data, existing conditions, and other thematic data, using Geographic Information System. The results showed that there had been a reduction in the area from paddy fields to non-paddy fields of 2,992.88 hectares from 2017-2021. It is dominated by conversion from paddy fields to oil palm areas of 2,795.58 hectares. The conversion suitability of paddy fields to non-paddy fields in 2017-2021 against Labuhanbatu Utara regional spatial plan is 21.92 percent, while 78.08 percent is not. To maintain food security in Labuhanbatu Utara Regency, the government should tighten supervision of the implementation of the regional spatial plan as well as increase the allocation of paddy fields.